Pain experienced by infants and toddlers at urine collection bag removal: A randomized, controlled, clinical trial. (July 2019) - Lamy, Charles; Loizeau, Valérie; Couquet, Catherine; Sturtzer, Caroline; Fluteau, Coralie; Dugas, Manon; Labrunie, Anaïs; Marin, Benoît; Desfougères, Jean-Luc; Bahans, Claire; Guigonis, Vincent; Beloni, Pascale
Abstract: Background: In pre-continent children, collection bags are frequently used as a first-line option to obtain a urine specimen. This practice, acknowledged by several guidelines for the step of UTI screening, is driven by a perception of the technique as being more convenient and less painful. However, our own experience led us to consider bag removal as a painful experience. Objective: Our aim was to determine whether the use of an oleo-calcareous liniment to aid bag removal reduced the acute pain expressed by young children. Methods: This prospective, randomized, controlled, single blind study was carried out in two emergency pediatrics departments. Pre-continent children aged 0–36 months admitted with an indication for urine testing were eligible for the study. Urine for dipstick test screening was obtained using a collection bag. At micturition, the patients were randomized into bag removal with (intervention group) or without (control group) liniment. Bag removal was recorded on video in such a manner as to permit independent assessments of pain by two evaluators blinded to group allocation. Pain was assessed using the FLACC scale. Findings: 135 patients were analyzed: 70 in the intervention group and 65 in the control group. The median FLACC scores [interquartile range] for the intervention and control groups, respectively 4.0 [2.0–7.0] and 4.0 [3.0–7.0], did not differ significantly (p = 0.5). A FLACC score ≥4 was obtained for 56% of the patients and a score ≥7 for 28%. Conclusion: Removal of urine collection bags caused moderate to severe pain in half of the children included. The use of an oleo-calcareous liniment did not reduce this induced pain.